PERANCANGAN SISTEM INFORMASI PENJUALAN BERBASIS WEB PADA TOKO SAMO - Jureka Samosir; Dimas Abisono Punkastyo (CV. Multi Kreasi Media, 2022)
Toko Samo is a store that is engaged in selling Korean fashion which still requires an expansion of the area in the sale and marketing of products provided both for customers within the city of Depok and outside Depok. Currently, the promotion of products sold at the Samo Store is only done using Whatsapp and Facebook, the recording of transactions at this store is also still manual so that it allows errors in recording and also allows data loss. At this time the method of purchasing at the Toko Samo is that customers go directly to the store to view and order the products provided. By building a web-based sales information system at the Samo Shop, it can help stores and customers in making buying and selling transactions, as well as helping companies promote products via the internet. This system will be developed using the Waterfall method and implemented using UML (Unified Modeling Language), PHP and Mysql. The results of this study are in the form of designing a web-based sales system that can be implemented properly by the company in order to promote products and make buying and selling transactions easily to customers.